Program Evaluation of Independent Campus Learning Program (MBKM) in IAIN Ternate Kirkpatrick Model - Adam, Adiyana; Sebe, Kamarun M.; Limatahu, Kartini; Jaohar, Yuliyani (International Journal of Trends in Mathematics Education Research, 2023)
Education has an important role in people's lives and in the future, with the hope that improving the quality of education can reduce crime rates. The Independent Campus Learning Program (MBKM) is a government initiative to increase student productivity and reduce truancy in tertiary institutions. MBKM aims to improve the quality of human resources, graduates, and educational institutions. This research focuses on the IAIN Ternate campus, especially the Faculty of Tarbiyah and Teaching Science (FTIK) which has 8 study programs. The research method used is qualitative and quantitative (Mix Method). Researchers used the draft MBKM guidelines from the FGD results to create variable indicators and create research instruments. The instrument was validated by three education experts using a Likert scale. The results showed that the implementation of the first level of MBKM (Reaction) had not been fully socialized to the study program coordinators. The guidelines used are still in draft form and have not been approved by the chancellor, indicating that the campus has not been wholeheartedly involved in implementing MBKM. The MBKM guideline draft is also still imperfect and is in the data collection stage regarding the number of credits of courses that will be involved in the MBKM.